Socioeconomic disparities in surveillance and follow‐up of patients with thoracic aortic aneurysm. Issue 4 (6th December 2021) - Shang, Michael; Weininger, Gabe; Mori, Makoto; Kahler‐Quesada, Arianna; Degife, Ellelan; Brooks, Cornell; Yousef, Sameh; Williams, Matthew; Assi, Roland; Geirsson, Arnar; Vallabhajosyula, Prashanth
Abstract: Background: Thoracic aortic aneurysm (TAA) is a significant risk factor for aortic dissection and rupture. Guidelines recommend referral of patients to a cardiovascular specialist for periodic surveillance imaging with surgical intervention determined primarily by aneurysm size. We investigated the association between socioeconomic status (SES) and surveillance practices in patients with ascending aortic aneurysms. Methods: We retrospectively reviewed records of 465 consecutive patients diagnosed between 2013 and 2016 with ascending aortic aneurysm ≥4 cm on computed tomography scans. Primary outcomes were clinical follow‐up with a cardiovascular specialist and aortic surveillance imaging within 2 years following index scan. We stratified patients into quartiles using the area deprivation index (ADI), a validated percentile measure of 17 variables characterizing SES at the census block group level. Competing risks analysis was used to determine interquartile differences in risk of death before follow up with a cardiovascular specialist. Results: Lower SES was associated with significantly lower rates of surveillance imaging and referral to a cardiovascular specialist. On competing risks regression, the ADI quartile with lowest SES had lower hazard of follow‐up with a cardiologist or cardiac surgeon before death (hazard ratio: 0.46 [0.34, 0.62], p < .001). Though there were no differences in aneurysm size at time of surgical repair, patients in the lowest socioeconomic quartile were more frequently symptomatic at surgery than other quartiles (92% vs. 23%–38%, p < .001). Conclusion: Patients with lower SES receive less timely follow‐up imaging and specialist referral for TAAs, resulting in surgical intervention only when alarming symptoms are already present.